WORKSHOP PENGELOLAAN WEBSITE DAN MEDIA SOSIAL DALAM BINGKAI MODERASI BERAGAMA DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN KRISTEN IAKN - Palelleng, Srivan; Pongdatu, Gideon A.N.; Rusman, Juprianus; Patandung, Suryaningsih; Pasinggi, Eko Suripto; Garonga, Melki; Upa, Samrius; Damayanti, Irene Devi; Padang, Semuel Yacobus (TONGKONAN: JURNAL PENGABDIAN MASYARAKAT, 2023)
The use of websites and social media has become an integral part of our digital era, facilitating communication, information sharing, and connecting people globally across diverse cultural and religious backgrounds. This workshop aims to provide participants with a strong understanding of the importance of managing websites and social media relevant to their goals, teaching best practices in content creation, management, and optimization, and helping participants understand associated risks and ways to address issues. The workshop also provides insights into the latest trends in digital marketing, analytics, and performance measurement for sustainable growth. IAKN Toraja, an institute managing various faculties, including the Faculty of Christian Education and Pedagogy, faces challenges in the underutilization of its website due to a lack of staff knowledge. Based on the identified issues with partners and post-training evaluations, it can be concluded that the WordPress platform can be effectively used by faculty and staff at IAKN Toraja to design their respective program study websites. This enables them to utilize websites as digital promotional tools at IAKN Toraja. During the evaluation session, participants proposed the implementation of advanced training. This advanced training aims to provide a deeper understanding and necessary skills for them to optimally manage websites in the promotion of their study programs. Thus, the development of these advanced skills is expected to enhance the efficiency and effectiveness of using websites as promotional tools at IAKN Toraja. Keywords: FKIPK, IAKN, promotion, Website, WordPress